Phosphonopeptides Revisited, in an Era of Increasing Antimicrobial Resistance - Marrs, Emma C.L. (Molecules, 2020)
Given the increase in resistance to antibacterial agents, there is an urgent need for the development of new agents with novel modes of action. As an interim solution, it is also prudent to reinvestigate old or abandoned antibacterial compounds to assess their efficacy in the context of widespread resistance to conventional agents. In the 1970s, much work was performed on the development of peptide mimetics, exemplified by the phosphonopeptide, alafosfalin. We investigated the activity of alafosfalin, di-alanyl fosfalin and β-chloro-L-alanyl-β-chloro-L-alanine against 297 bacterial isolates, including carbapenemase-producing Enterobacterales (CPE) (n = 128), methicillin-resistant Staphylococcus aureus (MRSA) (n = 37) and glycopeptide-resistant enterococci (GRE) (n = 43). The interaction of alafosfalin with meropenem was also examined against 20 isolates of CPE. The MIC(50) and MIC(90) of alafosfalin for CPE were 1 mg/L and 4 mg/L, respectively and alafosfalin acted synergistically when combined with meropenem against 16 of 20 isolates of CPE. Di-alanyl fosfalin showed potent activity against glycopeptide-resistant isolates of Enterococcus faecalis (MIC(90); 0.5 mg/L) and Enterococcus faecium (MIC(90); 2 mg/L). Alafosfalin was only moderately active against MRSA (MIC(90); 8 mg/L), whereas β-chloro-L-alanyl-β-chloro-L-alanine was slightly more active (MIC(90); 4 mg/L). This study shows that phosphonopeptides, including alafosfalin, may have a therapeutic role to play in an era of increasing antibacterial resistance.